2011
DOI: 10.1017/s0144686x10001182
|View full text |Cite
|
Sign up to set email alerts
|

Developing a carer communication intervention to support personhood and quality of life in dementia

Abstract: Dementia and dementia care present huge and growing challenges, both to individuals and to societies worldwide. In the United Kingdom, the context for the study reported here, recent key policy initiatives have highlighted problems in care provision, noting a lack of appropriate carer guidance, and an overemphasis on strictly biomedical interventions. Communication practices which support agency and empowerment have been identified as areas for particular improvement. A number of communication training and gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…A person-centred care approach places an emphasis upon dynamic attunement, which highlights factors such as the significance of the communicative cues of individuals with dementia and the need to adopt an open approach that enables a person with dementia to take the conversational lead (Kitwood & Bredin, 1992). Yet as noted by Young, Manthorp, Howells, and Tullo (2011), many communication skills training interventions for the carers of people with dementia appear to assume communication is based on keeping speech simple, maintaining eye contact and removing distractions. Gentry (2011) assumed that a person living with dementia knows what they are trying to communicate but are simply struggling with word finding.…”
Section: Conceptual Basismentioning
confidence: 99%
See 1 more Smart Citation
“…A person-centred care approach places an emphasis upon dynamic attunement, which highlights factors such as the significance of the communicative cues of individuals with dementia and the need to adopt an open approach that enables a person with dementia to take the conversational lead (Kitwood & Bredin, 1992). Yet as noted by Young, Manthorp, Howells, and Tullo (2011), many communication skills training interventions for the carers of people with dementia appear to assume communication is based on keeping speech simple, maintaining eye contact and removing distractions. Gentry (2011) assumed that a person living with dementia knows what they are trying to communicate but are simply struggling with word finding.…”
Section: Conceptual Basismentioning
confidence: 99%
“…Note 1. Based on previous consultations with key stakeholders, 'family carers' is used for informal carers and 'people living with dementia' for those they are supporting (Farina et al, 2017;Young, Manthorp, Howells, & Tullo, 2011).…”
mentioning
confidence: 99%
“…According to the findings of seven studies (Moyle et al, 2011;Woods et al, 2014;Clare et al, 2014b;Nikmat et al, 2015;O'Rourke et al, 2015;Orpwood et al, 2007;and Moyle et al, 2015) it is suggested that higher quality of relationship with family, friends, neighbours and caregivers, either family caregivers or care staff, is associated with increased QoL of elderly people with dementia. In addition, effective communication with their caregivers for elderly people with dementia will enhance their QoL (Young et al, 2011;Orpwood et al, 2007). Social connection with family, community and nature, such as gathering and talking with family, friends, and neighbours (Marventano et al, 2015;Moyle et al, 2015;Moyle et al, 2011;O'Rourke et al, 2015;Castillo et al, 2010;Gräske et al, 2015;Byrne et al, 2006;Orpwood et al, 2007), access to nature (Orpwood et al, 2007), and participation in social activities like organised outside activities (Moyle et al, 2015;Silberfeld et al, 2002;Orpwood et al, 2007), contribute to a higher level of QoL for 23 elderly people with dementia.…”
Section: Social Factorsmentioning
confidence: 99%
“…Especially, QoL of residents with dementia could be impaired with depressive mood (Black et al, 2012;Beerens et al, 2014). In addition, effective communication with caregivers is one of the preferred factors influencing the QoL from caregivers' perspectives Young et al, 2011). The last factor is concerned with the characteristics of care institutions.…”
Section: Factors From Different People's Perspectivementioning
confidence: 99%
“…Official statistics indicate that a very small proportion of carers (6 per cent) received assessments of their own needs in 2009/10 and that only 66 per cent of all those assessed received a service (Department of Health, 2010a;Niblett, 2011). Whilst information may have some potential to empower, when offered in a context constrained by resource limitations and unconnected to wider sources of empowerment, such as enhancement of carers' rights, its capacity to do so is severely limited (Matka et al, 2010;Young et al, 2011). Traditional practice tends to focus on providing information.…”
Section: 'Empowerment' and Carersmentioning
confidence: 99%